Concept of financial private (legal) relationship - Pratasavitski, Sergey (Journal of the Belarusian State University. Law, 2019)
The concept of financial private (legal) relationship is researched on the basis of the triad philosophical categories (things, attributes and relationship). It is noted that a key attribute of subject of finance which generates such a relationship appears possession of financial property. There are two types of private financial relationship. In the first type of the relationship, a possessor of financial property has a correspondent who does not have this particular property. The second type of relationship is expressed by joint possession of the same financial property. In the view of the author private financial relationship is a relationship of private subjects of finance determined by possession of financial property. Private-law attributes of subjects of finance give legal form to financial private relationship. The author concludes that financial private legal relationship is a relationship of subjects of private law determined by their private-law attributes associated with possession of financial property.
Keywords: possession of financial property; financial private relationship; financial private legal relationship